If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 3(2t + -3) + -1(4t + 3) + -7 = 0 Reorder the terms: 3 + 3(-3 + 2t) + -1(4t + 3) + -7 = 0 3 + (-3 * 3 + 2t * 3) + -1(4t + 3) + -7 = 0 3 + (-9 + 6t) + -1(4t + 3) + -7 = 0 Reorder the terms: 3 + -9 + 6t + -1(3 + 4t) + -7 = 0 3 + -9 + 6t + (3 * -1 + 4t * -1) + -7 = 0 3 + -9 + 6t + (-3 + -4t) + -7 = 0 Reorder the terms: 3 + -9 + -3 + -7 + 6t + -4t = 0 Combine like terms: 3 + -9 = -6 -6 + -3 + -7 + 6t + -4t = 0 Combine like terms: -6 + -3 = -9 -9 + -7 + 6t + -4t = 0 Combine like terms: -9 + -7 = -16 -16 + 6t + -4t = 0 Combine like terms: 6t + -4t = 2t -16 + 2t = 0 Solving -16 + 2t = 0 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 2t = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 2t = 0 + 16 2t = 0 + 16 Combine like terms: 0 + 16 = 16 2t = 16 Divide each side by '2'. t = 8 Simplifying t = 8
| 6*x=216 | | 5x^2-x-4x^2-12=0 | | -16-4-8= | | -(2y+4)+3(2y+4)-2y= | | ax-b=d-cx | | 4x^4-5x^3-2x^2=0 | | -10+6=-7x+-9 | | 3-4x-5=-2 | | 0.25(12+4x)-0.5(8+2x)=0 | | 5x+6y-17=0 | | -8x+3(1-8x)=-4x+31 | | 0.25(12+4x)-0.5(8+2x)= | | x^3*x^6*x^9= | | 5=-3b-4-3 | | 3x^3+16x^2+15x-18=0 | | 11=n/6-5 | | 2x-8=-3x+2 | | 1-3p-1=-18 | | 11-7x=107-28x | | 21=43-2r | | 2(x+3)=x-13 | | 52=5d+7 | | w-22= | | a/12-3=2 | | 2(x+3)+4x=6+6x | | 69-2x=16x+19 | | 1.3(x-13)=14 | | 9x+20y=85 | | 6x^3+7x^2-3x= | | -10x=2x^2 | | .5n+5n=7n-18 | | -5x+8x-33=21 |